The Effect of Eco-Efficiency, Enviromental Cost, and Intellectual Capital on Firm Value - Meily Surianti; Naomi Yolanda Silalahi; Jojor Lisbet Sibarani (Jurnal Akuntansi dan Keuangan, 2026)
This study investigates the association between firm Value and three key non-financial metrics: eco-efficiency, environmental costs, and intellectual capital. The study uses 99 secondary data observations, comprising annual and sustainability reports from mining sector companies listed on the Indonesia Stock Exchange between 2021 and 2023. Multiple linear regression, performed in SPSS version 29, was used for data analysis. Our findings reveal that intellectual capital significantly affects firm Value, while both eco-efficiency and environmental costs don’t affect firm Value.